Client's experiences of their shoulder pain and disability - A. Coole; R. de Jager; J. Hofmeyr; S. McKenzie; N. von Broembsen (AOSIS, 2000)
The purpose of this qualitative study was to enhance understanding of what it is like to suffer from chronic shoulder pain from the perspectives of those living with the experience. Unstructured interviews, using the open-ended question "tell us about your shoulder", were used to allow the twelve clients to elaborate freely on their feelings and experiences. Interviews were recorded and transcribed verbatim. These transcriptions were coded and categorized. Five themes emerged from the categories: Pain, Activities, Emotional Responses, Relationships and Coping Mechanisms. These findings expand understanding about quality of life for clients living with chronic shoulder pain and disability.